2018
DOI: 10.1590/1807-7692bar2018170119
|View full text |Cite
|
Sign up to set email alerts
|

Measuring accrual-based IPSAS implementation and its relationship to central government fiscal transparency

Abstract: This study aims to explore government accrual-based IPSAS implementation level measurements and to test the measures associated with central government fiscal transparency. Performing content analysis and Confirmatory Factor Analysis (CFA) on a sample covering 77 countries from 2008 to 2015, measurement indicates the relative importance and significance of financial performance statements and accrual accounting policies, such as nonexchanged and exchanged transactions as accrual level constructors. Conducting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(31 citation statements)
references
References 49 publications
1
24
0
6
Order By: Relevance
“…Unlike the cash-based standard, accrual-based IPSAS provide more accurate information not only on cash flows but also on revenue, cost, assets, liability and equity (PwC, 2012; Ijeoma and Oghoghomeh, 2014; Sellami and Gafsi, 2018). They ensure better performance service and maintain long-term fiscal sustainability (Kartiko et al , 2018). They also provide better measurement tools for financial performance and financial position (Ijeoma and Oghoghomeh, 2014; ACCA, 2017).…”
Section: Historical Background and Literature Reviewmentioning
confidence: 99%
“…Unlike the cash-based standard, accrual-based IPSAS provide more accurate information not only on cash flows but also on revenue, cost, assets, liability and equity (PwC, 2012; Ijeoma and Oghoghomeh, 2014; Sellami and Gafsi, 2018). They ensure better performance service and maintain long-term fiscal sustainability (Kartiko et al , 2018). They also provide better measurement tools for financial performance and financial position (Ijeoma and Oghoghomeh, 2014; ACCA, 2017).…”
Section: Historical Background and Literature Reviewmentioning
confidence: 99%
“…The inclusion of this category is motivated by the debate among academics and practitioners about public-sector accounting and accountability (Manes-Rossi et al, 2020), which has shown that academic research has had a moderate impact on accounting practices (Steccolini, 2019). Indeed, the results emerging from the analysis (Figure 12) support the idea of such a limited influence, as 73 out of the 78 articles (about 94%) were written by academics, while only four articles (von Hagen and Wolff, 2006;Cheng et al, 2010;Melo et al, 2014;Kartiko et al, 2018) were written by a team that included at least one practitioner.…”
Section: Authorsmentioning
confidence: 89%
“…Saat ini, standar akuntansi berbasis akrual yang dapat digunakan oleh pemerintah dan entitas sektor publik lainnya di seluruh dunia adalah International Public Sector Accounting Standards (IPSAS). Namun, meskipun IPSAS telah ditunjuk sebagai referensi dalam penyusunan laporan keuangan di dunia, masih terdapat negara yang menerapkan basis akrual tetapi tidak mengacu pada IPSAS (Kartiko et al, 2018). Salah satu contohnya adalah Amerika Serikat, yang mengacu pada Generally Accepted Accounting Principles (GAAP) (Sanko & Koldovskyi, 2017 (Boolaky et al, 2020).…”
Section: Penelitian Terdahuluunclassified